PENINGKATAN PENGETAHUAN DAN KETRAMPILAN KADER POSYANDU DI KELURAHAN PURWOSARI KECAMATAN MIJEN KOTA SEMARANG - Erma Handarsari; Agustin Syamsianah; Rahayu Astuti (Universitas Muhammadiyah Semarang, 2015)
Indonesia still have nutritional problems that requires serious handling. Posyandu (Integrated Service Post) is part of a society which is the spearhead in the implementation of government programs especially those related to health issues. In this case, including nutrition problems in the handling of malnutrition. Health officials cooperating with the cadres Posyandu in supplementary additional meal/food and monitoring weight gain. The goal in this devotion is to increase the cadre's ability to manage the Posyandu, nutritional knowledge and creativity to made additional meal/food for toddler to achieve optimal health care in Posyandu. The method used is counseling, guidance, practice and competition between cadres that can increased ability as a volunteer in society service. The sample in this devotion is 37 cadres residing in the village Purwosari, Mijen district ,Semarang City. Results of this devotion showed increased abilities, knowledge and skills of cadres,. The results of pre-test and post-test all the training materials showed an increased level cadre's knowledge. While the increase in skill can be seen from variability of ten kinds of dishes snack menu creativity of the cadre's results.Keywords : Posyandu cadres, knowledge, skills